FOOD SAFETY SITUATION AT MARKETS IN BAC NINH PROVINCE IN 2020 (Vietnam Journal of Community Medicine, 2022)
Objective: Describe the actual safety situation at markets in Bac Ninh province and identify somerelated factors.Methods: A cross-sectional descriptive study from May 2020 to December 2020 from 384 foodbusiness establishments in 32 markets in Bac Ninh province.Results: 16.3% of unprocessed food sellers and 15.3% of processed food sellers owned food safetycertificates. Unprocessed foods and processed foods at the markets were mainly grown in Bac Ninhprovince and purchased from households. The percentage of correct food safety knowledge washigh, 72.5% in unprocessed foods and 70.8% in processed foods. However, the rate of good practiceof food safety was low, only 25.8% in unprocessed foods and 16.7%.In the group of unprocessed foods, 81.9% of meat samples were contaminated with E.coli, of which44.4% of samples contaminated with E.coli exceeded the allowable limit; 1.39% of samples detectedbanned substance salbutamol; 55.6% of fish and shrimp samples were found to be infected withE.coli, of which 4.17% of samples were infected beyond the allowable limit; 19 samples of freshfruits and vegetables, instant fruit with residues of pesticides. Processed food group: 100% of saltedvegetables and fruits samples contaminated with aerobic microorganisms exceeding the allowablelimit; 97.9% samples of pork/spring rolls were contaminated with aerobic microorganisms; 93.6%samples of vermicelli/banh pho were contaminated with aerobic microorganisms. There is astatistically significant relationship between the practice of the pass food trader and the test resultsof the passed food samples.
Keywords: Food safety, unprocessed food, processed food, market, Bac Ninh.